A responsabilidade social da Ciencia da Informacao e/ou o olhar da consciencia possivel sobre o campo cientifico - Freire, Isa Maria (2001)
A model proposed by Wersig is used to weave, with the interdisciplinary threadmill of information science a conceptual netwok to aprehend the proper sense of an event occurred in a scientific field. The event in question was an article written in 1975 by Gernot Wersig and Ulrich Neveling proposing as a fundamental/basis for information science the social responsability of knowledge transmission